KONVIVIAL DALAM FILM â€œKINGSMANâ€ KARYA MATHEW VAUGHN - Nender, Oliver Othniel; Pelealu, Hetty; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  AbstractÂ  Â  Â  Â  Â This research entitled â€œConvivial in the Film Kingsman by Mathew Vaughnâ€. Convivial act as a part of Illocutionary is not only found in our daily life, but also in literary studies such as novel, drama, short stories, novella and film. The aims of this research are to identify, classify, and analyze the utterances and the function of convivial in the Kingsman film. This research used a descriptive method. The data were collected from conversation among characters, then they identified, classified and analyzed they are according to the concept of Leech (1983). The research showed that the convivial act can be categorized into five categories, those are offering, inviting, greeting, congratulating, and thanking, and how the function of convivial act used by the characters. It is expected that this study will help students and readers in learning pragmatics especially on convivial functions found in the film. _____________________________________Keywords: Convivial Act, Pragmatic, Film Kingsman